PELATIHAN PLYOMETRIC DENGAN DEPTH JUMP MENINGKATKAN DAYA LEDAK OTOT TUNGKAI LEBIH BESAR DARIPADA PELATIHAN STANDING JUMP PADA PEMAIN BOLA VOLI PUTRA - I Gede Widyatmika Pratama; Ketut Tirtayasa; Gde Ngurah Indraguna Pinatih; Putu Gede Adiatmika; Made Muliarta; Putu Adiartha Griadhi (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2018)
ABSTRACTBackground: Volleyball is a popular sport that is competitive. In volleyball, the volleyball player must play the volleyball over the net. The physical factor that supports that ability is explosion power of legs muscles. One of the ways to increase the explosion power of legs muscles is plyometric exercise. The exercises that were given in this research were plyometric depth jump and standing jump exercises to increase the explosion power of legs muscles. Purpose: The objective of this exercise is to compare the effect of both exercises for increasing the explosion power of legs muscles. Method: This research used experimental method Pre Test and Post Test Group Design in six weeks and frequency of three times a week. The samples are 22 people who are divided into two groups through ordinal pairing technique. The first group was given plyometric depth jump exercise and the second group was given standing jump exercise. The measurement of the explosion power of legs muscles used jump MD that was measured before and after exercises in every groups. Next, the average result was compared with statistical test of t- paired test. Result: The average of the explosion power of legs muscles pre test of the first group was 39.73 ± 3.74 centimeters and the post test was 55.64 ± 4.03 centimeters are statistically significant (p<0.05). Otherwise, on the second group, the pre test was 39.73 ± 3.58 centimeters and the post test was 51.36 ± 3.85 centimeters are statistically significant (p<0.05). The increasing of the explosion power of legs muscles between both groups are significant (p<0.05). The percentage of increasing of plyometric depth jump was 40.05% and for the standing jump was 29.27%. Conclusion: Plyometric depth jump increased the explosion power of legs muscles is bigger than standing jump exercise for all students on the men’s volleyball extracurricular of SMK Triatma Jaya Badung.Keywords : Plyometric depth jump and standing jump exercises, the explosion power of legs muscles, volleyball.